Rapid mapping of chromosomal breakpoints: from blood to BAC in 20 days - Lu, Chun-Mei (2009)
Structural chromosome aberrations and associated segmental or chromosomal aneusomies are major causes of reproductive failure in humans. Despite the fact that carriers of reciprocal balanced translocation often have no other clinical symptoms or disease, impaired chromosome homologue pairing in meiosis and karyokinesis errors lead to over-representation of translocations carriers in the infertile population and in recurrent pregnancy loss patients. At present, clinicians have no means to select healthy germ cells or balanced zygotes in vivo, but in vitro fertilization (IVF) followed by preim-plantation genetic diagnosis (PGD) offers translocation carriers a chance to select balanced or normal embryos for transfer. Although a combination of telomeric and centromeric probes can differentiate embryos that are unbalanced from normal or unbalanced ones, a seemingly random position of breakpoints in these IVF-patients poses a serious obstacle to differentiating between normal and balanced embryos, which for most translocation couples, is desirable. Using a carrier with reciprocal translocation t(4;13) as an example, we describe our state-of-the-art approach to the preparation of patient-specific DNA probes that span or ‘extent’ the breakpoints. With the techniques and resources described here, most breakpoints can be accurately mapped in a matter of days using carrier lymphocytes, and a few extra days are allowed for PGD-probe optimization. The optimized probes will then be suitable for interphase cell analysis, a prerequisite for PGD since blastomeres are biopsied from normally growing day 3 - embryos regardless of their position in the mitotic cell cycle. Furthermore, routine application of these rapid methods should make PGD even more affordable for translocation carriers enrolled in IVF programs.